A Novel and Compact Circularly Polarized Antenna for 5G Wireless Local Area Network Application - Ravikanti, Swetha; Anjaneyulu, L. (Electrical, Control and Communication Engineering, 2020)
The research paper presents a novel and compact circularly polarized (CP) antenna for a 5G wireless local area network (WLAN) application. It consists of a circular patch and a coaxial probe feed radiator. Circular polarization (CP) is attained by symmetric semi-circular slits of radius r1 at three edges of a circular path with 90° in direction, and the other semicircular slit is of different radius r2. To improve the impedance bandwidth and axial ratio, the radius of the fourth semicircular slit on circular patch antenna is varied. The design is verified by fabricating a compact antenna of 0.65λ0 × 0.65λ0 × 0.01λ0. The measured 10 dB impedance bandwidth is 3.9 % (5.36–5.56 GHz), 3-dB axial ratio bandwidth is 1.1 % (5.43–5.49 GHz) and gain of 6.6 dBi at resonant frequency of 5.37 GHz is obtained. The authors also describe two-dimensional radiation patterns of azimuth and elevation plane surface current distribution of the CP patch, VSWR < 2. The proposed CP antenna is suitable for the 5G WLAN application. The proposed design is compared with various techniques in literature and tabulated. The measured results are also discussed and they are in good agreement with simulated results.